Solar-driven chemical looping reforming of methane over SrFeO3-δ-Ca0.5Mn0.5O nanocomposite foam - Wang, Xinhe; Abanades, Stéphane; Chuayboon, Srirat; Zhang, Junshe; Wei, Jinjia (My University, 2022)
Strontium ferrite (SrFeO3-δ) is a very attractive oxygen transfer agent for chemical looping reactions and hydrogen-rich syngas generation. Dispersing SrFeO3 in a medium such as Ca0.5Mn0.5O could enhance the activity and cyclability. In this study, SrFeO3-δ-Ca0.5Mn0.5O (30 wt% SrFeO3-δ) nanocomposite with a reticulated foam structure was explored as the oxygen carrier for chemical looping reforming of methane in a solar tubular reactor. The foam nanocomposite was prepared by a hard-templating method. The performance was investigated at temperatures of 850–1000 °C and methane flowrates of 25–250 STP mL/min, and the oxidative gas was either CO2 or H2O in the oxidation step. In the reduction step of 27 successive redox cycles, the production rate of CO changed marginally and CO yield maintained at about 1.9 mmol/g, even though sintering occurred. The productivity of H2 decreased first and then tended to be stable at 3.8 mmol/g (i.e., twice the CO yield) as the cycling number increased (the average oxygen storage capacity of the material was ∼1.95 mmol/g). Microscopic and X-ray diffraction investigations suggested that the element distribution pattern and crystalline phase of the foam nanocomposite remained almost unchanged after 27 redox cycles, confirming material stability. The maximum solar-to-fuel efficiency for the foam nanocomposite was 5.68%, which was 21.4% higher than that for the powder nanocomposite. To increase syngas productivity and solar-to-fuel efficiency, it is required to conduct the reforming reaction at high temperatures and methane flowrates. However, the energy upgrade factor will decrease as methane flowrate increases.
Keywords: Chemical looping; Foam; Hydrogen-rich syngas; Methane reforming; Oxygen carrier; Solar energy